Análisis estructural comparativo de la superestructura del puente Santa Rosa – San Juan de Cumbaza en el distrito de Tarapoto – San Martín - Flores Arévalo, Renzo Renato (2014)
This thesis has been developed in the Academic Professional School of Civil Engineering, Faculty of Civil Engineering and Architecture, National University of San Martin - Tarapoto, for purposes of certification as a Civil Engineer with the working point the Town Center Santa Rosa - San Juan de Cumbaza in the District of Tarapoto, San Martin province and region. The research was conducted in order to make comparativa structural analysis of various types of superstructures of bridges proposed to determine their behavior in a way that allows us to perform an optimizad design the bridge Santa Rosa - San Juan de Cumbaza. So is actively involved in the production of new knowledge for positiva purposes of the community and science. Fundamental concepts required in the area of Structures, Solid Mechanics, Design Manual Bridges (AASHTO LRFD) and management of the relevant literature on the subject were applied; and support of structural engineering software SAP 2000 and CSI Bridge as tools allowed us the realization of the modeling of the structure, allowing near real behavior have results. As achievements, indicated that the results obtained show clearly that is possible, from the correct application of the theory, research and convincing results, which can be presentad as an alternativa technique for calculating the superstructures that form the third proposal, that is, two sections of bridge section composed of 17 m each and a central drawer metal are type hangers with their respective section of 56 m in length. The validation of the hypothesis of this research is achieved with the comparative analysis of the three alternativas presentad in superstructures being determinants bending, cutting moments, torsional, shear forces, axial, deformation, stiffness and dynamic behavior for earthquakes that may occur and, aware of our responsibility social as part of the National University of San Martin, we are contributing to pose a solution to the problem and incidentally contribute to economic and social development of the community, and therefore of our country, in addition to ensure that our knowledge is put into practica and develop our sense of professional career.